Meta‐analysis of behavioral self‐management techniques used by students with disabilities in inclusive settings. (25th August 2017) - McDougall, Dennis; Heine, Rumi C.; Wiley, Lori A.; Sheehey, Michael D.; Sakanashi, Keith K.; Cook, Bryan G.; Cook, Lysandra
Abstract : This comprehensive review synthesizes findings from 29 studies in which students with disabilities utilized behavioral self‐management techniques in inclusive settings. Findings suggest that consistent with 2 earlier reviews of these types of studies, most behavioral self‐management techniques continue to be adaptable in inclusive settings with moderate to strong efficacy. This review identifies strengths as well common limitations of the studies, provides recommendations for future research and practice, and includes behavioral self‐management resources.